Improving Mathematical Reasoning Skills Through an Open-Ended Approach Assisted by Google Classroom and Google Meet - Trisnawati, Nika Fetria; Setyo, Arie Anang; Sundari, Sundari; Warlatu, Abigael (Department of Mathematics Education Program IPI Garut, 2024)
Penelitian ini bertujuan untuk meningkatkan kemampuan penalaran matematis siswa melalui pemanfaatan Google Classroom dan Google Meet. Subjek penelitian adalah 21 siswa kelas XI SMK Negeri 2 Kota Sorong. Penelitian ini dilakukan dalam dua siklus, yaitu siklus I dan siklus II, dengan pendekatan penelitian tindakan kelas. Data dikumpulkan melalui penilaian hasil belajar dan observasi kelas, lalu dianalisis secara kuantitatif dan kualitatif. Hasil penelitian menunjukkan adanya peningkatan kemampuan penalaran matematis siswa pada berbagai indikator, yaitu: menyajikan proposisi dan ilustrasi matematika tertulis (47,43%-85,89%), melaporkan dan memanipulasi tuduhan matematika (36,80%-77,77%), menyusun data dan memberikan justifikasi solusi (44,20%-81,40%), serta mencapai kesimpulan (28,12%-47,39%). Rata-rata respons positif siswa terhadap pendekatan open-ended mencapai 9,5%. Berdasarkan temuan ini, pendekatan open-ended yang didukung oleh Google Classroom dan Google Meet terbukti efektif untuk meningkatkan kemampuan penalaran matematis siswa. Implikasi dari penelitian ini adalah bahwa integrasi teknologi dengan pembelajaran berbasis open-ended dapat diterapkan secara lebih luas untuk meningkatkan kualitas pembelajaran matematika di sekolah, terutama dalam situasi pembelajaran jarak jauh. This study aims to improve students' mathematical reasoning ability using Google Classroom and Google Meet. The subjects of the study were 21 grade XI students of SMK Negeri 2 Sorong City. This study was conducted in two cycles, namely cycle I and cycle II, with a classroom action research approach. Data was collected through assessment of learning outcomes and classroom observations, then analyzed quantitatively and qualitatively. The results of the study showed an increase in students' mathematical reasoning ability in various indicators, namely: presenting written mathematical propositions and illustrations (47.43%-85.89%), reporting and manipulating mathematical accusations (36.80%-77.77%), compiling data and providing justification for solutions (44.20%-81.40%), and reaching conclusions (28.12%-47.39%). The average positive response of students to the open-ended approach reached 9.5%. Based on these findings, the open-ended approach supported by Google Classroom and Google Meet has proven effective in improving students' mathematical reasoning skills. The implication of this study is that the integration of technology with open-ended learning can be applied more widely to improve the quality of mathematics learning in schools, especially in distance learning situations.